Refleksja nad projektem kodeksu urbanistyczno-budowlanego - Jaworski, Bartłomiej (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Presented analysis of the proposed changes, contained in the draft, provide an image of the future Polish construction law, which in some parts differs from the current one. In addition to changes in the names of some institutions, special attention should be paid to the reform of the structure of the construction supervision bodies, which seems to have far-reaching effects, particularly those measurable financially. Many of the problems observed today have not yet seen the required solutions, while others have only been solved casually without reaching their essence. Worrying is the conservatism of the Codification Committee in the use of such concepts as public interest, common good, or spatial order and lack of attempts at a redefinition. The project does not seem to correspond to the code requirement of universality, regulating matters that should be included in separate acts, and omittng those worth including in the code. Substantiated is the fear that the proposed provisions of the draft code will in effect lead to a permanent state of helplessness of the bodies which, as yet, have poorly interpreted the new standard. The code may not pass the first trial and may deprive investors of hope for a better quality of Polish construction law. Expected changes may not come, and it will be difficult for a discussion and amendment of the act which has just been discussed and adopted.
Keywords: prawo budowlane; kodyfikacja polskiego prawa budowlanego; projekt kodeksu urbanistyczno-budowlanego; kodeks urbanistyczno-budowlany